EFFECT OF METHANOL LEAF EXTRACT OF ORTHOSIPHON STAMINEUS BENTH. ON HEPATIC DRUG METABOLIZING ENZYMES IN SPRAGUE DAWLEY (SD) RATS - Chin Jin Han,; Abas Hj. Hussin,; Sabariah Ismail , (Tropical Life Sciences Research, 2008)
Orthosiphon stamineus Benth. or locally known as Misai Kucing is widely used in Malaysia for treating hypertension, urinary system ailments and kidney stone disease. This study aims to study the in vitro effect of methanol extract of O. stamineus on aminopyrine N-demethylase, UDP-glucuronosyltransferase (UGT) and glutathione-S-transferase (GST) activities in young male and female Sprague Dawley (SD) rat liver. Hepatocytes, liver microsomes and cytosolic liver fraction (S-9 fraction) from young male and female SD rats were used throughout the in vitro experiment to examine aminopyrine N-demethylase, UGT and GST activities. Results obtained showed that aminopyrine N-demethylase activities in young male female and rat liver were not affected by methanol extract of O. stamineus except at 0.001 mg/ml (P < 0.05) in female rats. However, most of the UGT and GST activities in young male and female SD rat liver were significantly decreased by methanol extract of O. stamineus treatment especially at the higher concentrations such as 0.1 mg/ml and 1 mg/ml as compared to their control group. In conclusion, concentrations of methanol extract of O. stamineus from 0.00001 mg/ml to 0.0001 mg/ml did not affect the activities of aminopyrine N-demethylase, UGT and GST in young male and female SD rat liver. Methanol extract of O. stamineus higher than 0.0001 mg/ml had a greater influence on UGT and GST activities than the aminopyrine N-demethylase activities in SD rat liver and the effects were dose-dependent. Orthosiphon stamineus Benth. atau dikenali dengan nama tempatan sebagai Misai Kucing digunakan secara meluas di Malaysia untuk rawatan hipertensi, masalah sistem urinasi dan penyakit batu karang ginjal. Kajian ini bertujuan untuk mengkaji kesan in vitro ekstrak metanol O. stamineus ke atas aktiviti aminopirin N-demetilase, UDP-glukuronosiltransferase (UGT) dan glutathione-S-transferase (GST) di dalam hati tikus jantan dan betina muda Sprague Dawley (SD). Hepatosit, mikrosomal dan fraksi sitosolik (fraksi S-9) daripada hati tikus jantan dan betina muda telah digunakan sepanjang eksperimen in vitro ini untuk menguji aktiviti aminopirin N-demetilase, UGT dan GST. Keputusan yang didapati menunjukkan ekstrak metanol O. stamineus tidak mempengaruhi aktiviti aminopirin N-demetilase di dalam hati tikus jantan dan betina SD kecuali pada 0.001 mg/ml (P < 0.05) pada tikus betina. Walau bagaimanapun, kebanyakan aktiviti UGT dan GST di dalam hati tikus jantan dan betina dikurangkan secara signifikan oleh ekstrak metanol O. stamineus terutamanya pada kepekatan yang lebih tinggi seperti 0.1 mg/ml dan 1 mg/ml jika dibandingkan dengan kumpulan kawalan. Secara kesimpulan, kepekatan ekstrak metanol O. stamineus daripada 0.00001 mg/ml sehingga 0.0001 mg/ml tidak mempengaruhi aktiviti aminopirin N-demetilase, UGT dan GST di dalam hati tikus jantan dan betina muda SD. Kepekatan ekstrak metanol O. stamineus yang lebih tinggi daripada 0.0001 mg/ml mempunyai kesan yang lebih besar ke atas aktiviti UGT dan GST jika dibandingkan dengan aktiviti aminopirin N-demetilase di dalam hati tikus SD dan kesannya adalah berkadaran dengan dos.